The GDR's foreign trade policy - Ulrich Dietsch (Intereconomics, 1976)
Before the German Democratic Republic (GDR) achieved worldwide political recognition in 1972 and 1973 many Western observers were of the opinion that the GDR's trade with Western industrialised countries was still not very developed. A closer look at this field of activity shows, however, a different picture.
Keywords: 330; East-West Relations